Mental Health and Subjective Well-being of Individuals With Ménière's: Cross-sectional Analysis in the UK Biobank. Issue 5 (June 2015) - Tyrrell, Jessica; White, Mathew P.; Barrett, George; Ronan, Natalie; Phoenix, Cassandra; Whinney, David J.; Osborne, Nicholas J.
Abstract : Hypothesis: Ménière's disease significantly impacts on an individual's mental health and subjective well-being (SWB). Background: Ménière's disease is an unpredictable illness that impacts on mental health. The symptom triad of vertigo, tinnitus, and hearing loss all contribute to the disabling nature of the condition. To date, limited research has investigated the mental health and SWB impact of Ménière's disease. Methods: We investigated the mental health and SWB of 1, 376 Ménière's sufferers in the UK Biobank and compared this to over 500, 000 controls. Participants in the Biobank were asked 38 questions pertaining to mental health and SWB. We utilized crude and adjusted linear and logistic regression to investigate the association between Ménière's and mental health and SWB. We also investigated how mental health and SWB might be related to length of diagnosis to see whether people might adapt to Ménière's over time. Results: Ménière's was associated with increased frequency of depression, tiredness, tenseness, and unenthusiasm in the 2 weeks before recruitment. Ménière's was associated with longer periods of depression than controls (10.2 wk [95% CI: 5.2–15.2 wk]). Reduced health satisfaction was associated with Ménière's, but in other aspects of life (general happiness, work, family, friends, financial), individuals with Ménière's were as happy as controls. Mental health and SWB in individuals diagnosed for longer was better than in those who were recently diagnosed suggesting at least partial adaptation. Discussion: This is the largest population study investigating the mental health impact of Ménière's. Our findings suggest that Ménière's adversely impacts on mental health, an individual's emotional state, and their life satisfaction. However, our findings raise the importance of supporting social relations for people with Ménière's and that although a cure is not currently available, we can still learn much about the adaptation strategies developed by long-term sufferers to help individuals with new diagnoses. Abstract : Supplemental digital content is available in the text.